Manusia dan Pelestarian Lingkungan: Perspektif Tafsir Maqāṣidī dalam Penanganan Sampah Plastik - Rohma, Dika Purnama Aulia; Putri, Lintang Dewi Fi’liya (Canonia Religia, 2024)
Plastic pollution has become a global crisis that endangers the environment and human health. One of the main causes of pollution due to plastic waste is the characteristics of plastic which takes a long time to decompose. The use of plastic is not only risky for human health, but also has a major impact that threatens environmental sustainability. Using the perspective of maqāṣidī tafsir, this paper aimed to explore how Qur'anic values can serve as a theological foundation to address the plastic waste crisis, by relativizing Qur'anic teachings with modern scientific and social perspectives. The findings showed that plastic pollution harms ecosystems and health, contradicting the principles taught in the Qur'an, hadith, rules of fiqh, and maqāṣid al-sharī'ah. This research has compiled ten Qur'anic verses that are thematically related to environmental conservation. From these verses, it was found that verses such as QS. al-A'rāf: 56, al-Rūm: 41, and al-Mā'idah: 32 contain maqāṣid al-sharī'ah values such as ḥifẓ al-nafs and ḥifẓ al-bi'ah, which are very relevant in answering the plastic pollution crisis. Messages of non-damage, calls for ecological self-evaluation, and the importance of cross-party cooperation provide the ethical and spiritual foundation for building sustainable environmental awareness. The success of tackling plastic pollution depends on the active participation of the community, such as reducing single-use plastics, using reusable bags, and recycling. These actions are a form of responsibility and care for others and future generations.